Bahia, a terra do dendê: uma história transnacional e complexa do dendê - Castañeda, Vanessa (Afro-Ásia, 2022)
Resenha de: WATKINS, Case. Palm Oil Diaspora: Afro-Brazilian Landscapes and Economies on Bahia’s Dendê Coast. Cambridge: Cambridge University Press, 2021. 347 p.